P65 Why has emergency oxygen administration failed to improve despite 'best practice' interventions?. (14th November 2013) - Paranahewa, SG; Sithamparanathan, S; Taylor, R; Pepper, T; O'Shaughnessy, T; Ricketts, WM
Abstract : Introduction and Objectives: Despite instigating all operational and educational recommendations in the BTS Emergency Oxygen Guideline (local policy, standardised prescription and bedside documentation and training) our performance in the BTS annual Emergency Oxygen Audit has failed to improve, in line with national findings, with only 56% of oxygen prescribed, none signed for and 66.7% outside the target range at the most recent audit. Our aim was to investigate the reasons underlying this. Methods: A link to an online survey was emailed to all junior doctors and nursing staff on hospital mailing lists. The survey was designed to utilise Pathman's four stages of guideline compliance (awareness, agreement, adoption and adherence) (1). Results: Results are summarised in Table 1 . Free text comments focussed on a desire by both doctors and nurses for the prescription chart to be clearer and to be located in a more prominent area of the drug chart, whilst doctors were concerned their prescriptions were not followed, nurses commented that doctors frequently failed to prescribe oxygen correctly, if at all. Discussion: Responders reported good levels of awareness, agreement and adoption, yet adherence, as measured by audit, performance in prescribing and administration scenarios and an inability to locate guidelines on the Trust intranet would suggest that further intervention is required. The high level of belief that their own application of the guidelines, by both medical and nursing staff, is good would suggest that either this self-selected cohort perform better than their less interested peers or that lack of awareness, so called "unconscious incompetence"(2), is a concern. Generally the desire is for yet more training, however, our concern remains that this has limited effect and systems need to be strengthened to improve oxygen prescribing and administration. References: 1. Pathman et al . The awareness-to-adherence model of the steps to clinical guideline compliance. The case of paediatric vaccine recommendations. Medical Care 1996;34:873–89. 2. Conscious Competency - The Mark of a Competent Instructor. The Personnel Journal. 1974;53:538–9.